MEMBERDAYAKAN TENAGA KEPENDIDIKAN ANAK USIA DINI MELALUI PROGRAM SIMBIOSIS - Hidayat, Kurniawan Catur (JIV-Jurnal Ilmiah Visi, 2010)
Symbiotic programs provide alternative solutions to improve the quality of educators and teachers of non-formal education through the cooperation of mutual assistance between them. The programs provide a positive reciprocity between students majoring in Early Childhood Education and the teachers of Early Childhood Education in schools. The programs are conducted in the form of exchanging the theory and application of various knowledge of child education, media development, and "how to teach" development. Symbiotic programs provide a lot of positive value in improving the quality of teachers of early childhood education to increase their knowledge, skills, abilities, and expertise as educators as well as early childhood